Clinical aspects of reimbursement policies for orphan drugs in Central and Eastern European countries - Szczepan Jakubowski; Pawel Kawalec; Przemyslaw Holko; Iwona Kowalska-Bobko; Maria Kamusheva; Guenka Petrova; Pero Draganić; Pero Draganić; Leos Fuksa; Agnes Männik; Fanni Ispán; Vitalis Briedis; et al. (Frontiers Media S.A., 2024)
Objectives: The aim of this study was to characterize the reimbursement policy for orphan drugs (ODs) in Central and Eastern European (CEE) countries in relation to the availability and impact of clinical evidence, health technology assessment (HTA) procedure, selected economic indicators, and the drug type according to indications.Materials and methods: A list of authorized medicines with orphan designation and information about active substance, Anatomical Therapeutic Chemical (ATC) classification, and therapeutic area was extracted from the web-based register of the European Medicines Agency (EMA). A country-based questionnaire survey was performed between September 2021 and January 2022 in a group of selected experts from nine CEE countries (an invitation was sent to 11 countries). A descriptive and statistical analysis was conducted to determine statistical significance, correlations, between the drug or country characteristic and the positive recommendation or reimbursement of ODs.Results: The proportion of reimbursed orphan drugs differed between countries, ranging from 17.7% in Estonia to 49.6% in Hungary (p < 0.001). The odds that ODs were reimbursed were reduced in countries with a "strong" level of impact of drug safety and efficacy on reimbursement decisions (p=0.018), the presence of other additional specific clinical aspects (e.g., genomic data) considered in the reimbursement decision (p < 0.001) and mandatory (without exception) safety assessments (p=0.004). The probability that ODs were reimbursed was increased in countries with a "moderate" level of impact of drug safety and efficacy on reimbursement decisions (p=0.018), when reimbursement decisions are dependent on the EMA registration status and orphan drug designation (p < 0.001), the presence of the "positive HTA recommendation guarantees reimbursement" policy (p < 0.001), higher GDP per inhabitant (p=0.003), and higher healthcare expenditure (p < 0.001).Conclusion: We found that there are differences among CEE countries in the reimbursement of orphan drugs, and we identified aspects that may influence these differences. Safety, efficacy, and specific clinical aspect issues significantly influenced reimbursement decisions. Antineoplastic and immunomodulating agents drugs were the largest group of ODs and increased the chance of getting a positive recommendation. The higher GDP per inhabitant and healthcare expenditures per inhabitant were positively linked to the chance that an OD receives reimbursement.